Mini chamber system for long-term maintenance and observation of cultured cells. (February 2005) - Ho, Chung-Liang; Mou, Tun-Yi; Chiang, Pei-Shuan; Weng, Chu-Li; Chow, Nan-Haw
We constructed a mini chamber system that was able to maintain cell culture on a microscope for long periods. It is a modified closed system with medium perfusion and CO2 circulation. The closed CO2 circulation and ample air inside the chamber distinguish it from other closed systems. Using different cell lines, the system was shown to be able to support long-term, time-lapse recording. After 229 hours of time-lapse recording, A2058 cells (a melanoma cell line) became overconfluent but still multiplied. Many CAD cells (a murine neuron-like cell line) still moved their cell bodies and kept their neurite-like processes after 28 days of recording. The entire healing process of a scratch-wounded T24 (a bladder cancer cell line) monolayer can be monitored. Such a modified closed system should find many applications in developmental biology, cell biology, and cancer biology where long-term, time-lapse recording is required or when the health of cells is important.